Urban Market Metamorphosis: A visionary Design for Community Engagement - Mansi Yadav; Krishika Jindal; Pooja Lalit Kumar (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The city of Delhi transcends time, a harmony of rich history and pulsating contemporary life, unfolding its narrative as the very extension of people’s souls. The heart of Delhi are its markets, bridges connecting diverse cultures through changing times. The markets allow people to become threads of a communal fabric, knitting tales of shared experiences. Prioritizing community input through interviews and site studies establishes a clear understanding of local desires. The visionary urban market design titled “Mehfil” creates versatile spaces, incorporating traditional roles to meet the city’s diverse needs. The market is a fusion of enchanting urban design and romantic allure, blending modern functionality with local culture. Aiming for social engagement and economic growth , the market features a plethora of spaces hosting varied activities. Through multi-functional spaces, charming pathways, green spaces and courtyards, artistic murals and intricately decorated facades, “Mehfil” turns every visit into a celebration.